Monção Sul Americana: Variabilidades e impactos na paleopluviosidade dos Andes orientais durante os últimos 1400 anos a partir de estudos isotópicos em espeleotemas - Apaéstegui Campos, James Emiliano (2014)
The caves located in the Peruvian and Bolivian Andes are characterized by the presence of speleothems providing high potential for high resolution paleoclimate and paleohydrologicall reconstructions, which allow understand principally short periods of climate variability. These variability during the last millennium have been widely studied, mainly in correspondance to important recent weather events such as Medieval Climate Anomaly (MCA, AD 900 1200) and the Little Ice Age (LIA - 1400-1850 AD), which were associated to changes in solar and volcanic activities in the Northern Hemisphere. In this work, we used stable oxygen isotopes (δ 18O) in speleothems as a proxy for assessing the stages of change of sources and precipitation intensity related to changes in the activities of the South American Monsoon System. 5 espeleotems were analyzed; 2 in Palestina cave (Peru) and 3 in Chiflonkhakha cave (Bolivia). Our results show changes in δ 18O values suggesting dry conditions in Peru and humid conditions in Bolivia during ACM evidenced by more positive and negative values respectively. Later, during the LIA, results show more negative δ 18O values indicating more humid conditions in both regions. Analysis of frequencies over the studied records showed periodicities around 8, 25 and 64 years. These variations were correlated to ACM and LIA with other paleoclimatic reconstructions in marine and continental areas, in order to understand the influence of the zonal and latitudinal variability of ocean surface temperatures (SSTs) in the Equatorial Pacific and the Atlantic Ocean and it´s influence on distribution of rainfall in relation to the South American Monsoon.